Penggunaan Tes dalam Tes Formatif dan Tes Sumatif - Sukmayeti, Sukmayeti; Lahmi, Ahmad; Masnita, Delmi; Nurhamidar, Nurhamidar; Wahyuni, Yessi (TSAQOFAH, 2026)
This study aimed to analyze the role of tests in formative and summative evaluation as key components of the Islamic Education learning process. Formative evaluation is carried out during the learning process to monitor students’ progress, provide feedback, and support teachers in adjusting instructional strategies so that learning objectives can be optimally achieved, whereas summative evaluation is conducted at the end of an instructional unit to assess overall learning outcomes and to serve as a basis for academic decision-making, such as graduation or promotion to the next grade. This study employed a literature review method through a theoretical examination of various relevant sources on formative evaluation, summative evaluation, and the use of tests in the context of Islamic Education. The findings indicate that formative and summative evaluation have complementary functions, whereby formative evaluation is oriented toward the learning process, while summative evaluation focuses on learning outcomes. The assessment techniques used also differ according to their respective purposes, including observation, discussion, and self-assessment in formative assessment, as well as written tests, portfolios, and projects in summative assessment. These findings affirm that the appropriate implementation of formative and summative evaluation can enhance the quality of learning, identify students’ strengths and weaknesses, and support more objective and sustainable instructional decision-making within the framework of Kurikulum Merdeka.